Exploring the potential anti-senescence effects of soybean-derived peptide Soymetide in mice hippocampal neurons via the Wnt/β-catenin pathway - Garg, Asmita; Saroj, Jyotshana; Tiwari, Saurabh; Das, Uttara; Shukla, Neetu; Ghosh, Jimut Kanti; Bandyopadhyay, Sanghamitra (Frontiers in Pharmacology, 2025)
Soybean-based foods enhance cognitive functions by influencing hippocampal mechanisms. These salutary effects have so far been attributed to isoflavones present in soybeans. Considering cellular senescence contributes to cognitive decline and that no specific soy-derived peptides are known for their potential to mitigate senescence, we examined the efficacy of a thirteen amino acid soy-derived peptide, Soymetide, on a doxorubicin-induced senescence mice model. Soymetide pretreatment lowered the senescence markers p53, p21 and p16, pro-inflammatory cytokines, and Senescence β-Galactosidase staining while enhancing the mature neuronal marker NeuN in the hippocampus. This anti-senescent effect was comparable with that of a well-known senolytic combination (dasatinib and quercetin). Research indicates that Wnt signaling influences cellular senescence, and our findings here demonstrate that doxorubicin decreased hippocampal Wnt3a, p-LRP6, Frizzled, Dishevelled, Axin1, and β-catenin levels and increased GSK-3β, while Soymetide mitigated these effects. Additionally, upon inhibition of the Wnt/β-catenin pathway, Soymetide’s ability to reduce senescence markers and restore NeuN expression was reduced. We validated the anti-senescence impact on hippocampal neurons by co-immunostaining Wnt/β-catenin and senescence indicators alongside NeuN in mice and assessed it in primary hippocampal neurons. Further examining the neuronal survival and functions revealed that Soymetide blocked the doxorubicin-induced loss in Nissl-stained surviving neurons and learning-memory performances, measured by Y-Maze and Passive Avoidance tests, which Wnt/β-catenin inhibitors could counteract. In conclusion, our study identifies a novel Wnt/β-catenin-linked mechanism of doxorubicin-induced senescence in the hippocampal neurons and demonstrates Soymetide’s effectiveness in reversing this process. Hence, this suggests Soymetide’s potential therapeutic application in addressing cognitive decline associated with cellular aging.